The Role of Outpatient Care Accreditation in Enhancing Foreign Patients' Perception of Colombian Medical Tourism: A Quasi-experimental Design - Mario Alberto de la Puente Pacheco PhD; Carlos Mario de Oro Aguado MSc; Elkyn Lugo Arias MSc; Briyis Fontecha Pacheco B.Sc (SAGE Publishing, 2020)
This study analyzes whether hospitals accredited by the Joint Commission International in outpatient medical care protocols located in Colombia achieve a higher quality perception from foreign patients compared to others treated in a non-accredited one. A t -test with Welch correction, chi-square test, correlation coefficient of Tau Kendall, pre-test, post-test, complementary questionnaire and a 2 focus groups were used in 178 foreign patients. It was observed that patients treated in accredited hospitals had a higher quality perception than the non-accredited group. However, it was found that an unbalanced application of the 3 variables negatively alters quality judgment. Findings contributes to understanding the Colombian medical tourism in depth using non-conventional instruments.